Role of inhaled corticosteroids/formoterol in relieving acute asthma as compared to traditional salbutamol in children 6 to 11 years old on maintenance and reliever therapy step 3 and above as per the Global Initiative for Asthma guideline - Danish Abdul Aziz; Werdah Viquar (Monaldi Archives for Chest Disease)
The recent Global Initiative for Asthma (GINA) guidelines offer two reliever therapy options for patients on step 3 and above: the more popularly used short-acting β-agonists (SABA) and the newly introduced inhaled corticosteroids (ICS)-formoterol combination. Our aim was to assess the effectiveness of the ICS/formoterol combination in comparison to the traditional SABA offered to patients aged 6-11 years old following step 3 and above of the GINA guidelines. A retrospective study was conducted at a tertiary care facility in Karachi, Pakistan. The study involved children aged 6-11 years old who were admitted with an asthma exacerbation and were subsequently discharged on step 3 and above as per the GINA guidelines for 3 months. The patients were then categorized into two groups depending on the type of reliever used (ICS/formoterol or salbutamol). There were 80 pediatric patients enrolled in our study. The emergency room visits with asthma exacerbation in 3 months following discharge were significantly lower in the ICS/formoterol reliever group (1.27±0.83) than in the salbutamol reliever group (1.93±1.36) (p=0.01). Mean admission with asthma in 6 months post-discharge was significantly higher in the salbutamol group (2.18±0.82) as compared to the ICS/formoterol group (1.24±0.83). Moreover, the number of patients requiring step-up control within 3 months of discharge was also significantly lower in the ICS/formoterol group, with 2 patients, than the salbutamol group, with 10 patients (p=0.02). The forced expiratory volume in 1 second value 3 months after discharge was significantly greater in the ICS/formoterol group (91.27±8.32) than in the salbutamol group (84.58±10.44) (p=0.02). Through our analysis, we were able to highlight the superiority of ICS/formoterol as a reliever compared to SABA for moderate asthma.